Evolución de la delincuencia en España según las estadísticas oficiales (1998-2005) - Serrano Gómez, Alfonso; Vázquez González, Carlos; Serrano Tárraga, M.ª Dolores; Luaces Gutiérrez, Ana Isabel; Serrano Maíllo, M.ª Isabel; Fernández Villazala, Tomás; García García-Cervigón, Josefina (Revista de Derecho Penal y Criminología, 2019)
-